Contemporary art in the Federal Republic of Germany : 12 collections of 30 graphics : Woodcut, Etching, Lithography. - Adriani, Götz (Stuttgart : IFA - Institut für Auslandsbeziehungen Stuttgart, 1979)
Antes, Horst ; Bremer, Uwe ; Gorella, Arwed ; Grieshaber, HAP ; Janssen, Horst ; Meckseper, Friedrich ; Minuzzi, Maurilio ; Oppermann, Wolfgang ; Pilgrim, Hubertus von ; Reichert, Josua ; Schultze, Bernard ; Sorge, Peter ; Wunderlich, Paul
Biog. [1 p.]
12 collections of 30 graphics. Each will provide a survey of contemporary graphic art in the Federal Republic of Germany in a sequence of exhibitions appearing at regular intervals. They are entitled "Tournee-Ring". (...) Planned and selected in 1974 by Dr. Götz Adriani, (...) Dr. Wulf Herzogenrath (...) Organized by the Institute for Foreign Cultural Relations
Engels
boek
Keywords: Duitsland